The impact of crossbreeding Egyptian and Italian buffalo on milk yield and composition under subtropical environmental conditions. Issue 2 (23rd May 2016) - Nasr, Mohammed AF
Abstract : Buffalo are the second most valuable species in the world for milk production and their milk prices have been based on fat and protein composition. The aim of the paper was to compare the milk yield and composition of pure Egyptian buffalo (EB) and their crosses with the Italian buffalo and to investigate the impact of temperature humidity index (THI) on milk yield and composition under subtropical stressful conditions. 516 lactating buffalo were used (152 EB; 176 F1 crosses 50% EB and 50% Italian buffalo and 188 back cross (BC) 75% EB and 25% Italian buffalo). The results revealed that, milk yield (5·79 and 10·32%) and peak yield (6·36 and 7·67%) were significantly higher in F1 and BC than in EB, respectively. BC had 7·74 and 3·67% significantly higher daily yield when compared with EB and F1, respectively. EB were robust in the hot condition as the only reduction was in the peak of milk production from 15·02 in low THI to 13·72 kg in high THI, but fat and total solids%, were increased from 5·61 and 16·31 THI in low to 7·01 and 17·59 in high THI, respectively. BC was similar to some extent to EB as their milk was similar to EB under sever hot climate conditions (2331·92 and 2327·50 kg, respectively). A statistically significant reduction in the average daily milk yields was detected only in F1 from 10·33 to 8·38 kg in low and high THI level, respectively. The current study showed that BC produced a higher milk with higher daily average milk yield and peak yield with some evidence of robust under sever hot condition which were approximately similar to EB. Thus, it is recommended to encourage the producers to increase the number of BC animals in their farm for improving the milk production to fulfil the demand of Egyptian markets.